Comparative Model of Single-phase AC Cycloconverter for 1000Wp Photovoltaic Grid-connected 220VAC-50Hz - Handoko Rusiana Iskandar; Yuda Bakti Zainal; Ana Urbaningtyas (Fakultas Teknik, 2022)
Currently, the Electrical Engineering Laboratory (EEL) of Universitas Jenderal Achmad Yani has a 1 kWp photovoltaic (PV) system. However, in order to fulfill the overall load, the hybrid link to the grid must be improved. The PV system and the grid must be synchronized in terms of voltage, frequency, and phase. This article presents comparative simulations of AC-AC converter models of power electronics component variants using MATLAB 2019a. Among other stages is to model the DC-DC Converter in order to enhance the output voltage of the solar panel by identifying the circuit characteristics. The second stage involves simulating the MOSFET-based DC-AC Converter circuit, which is used to convert DC to AC. The use of switching Thyristor, Gate Turn-Off Thyristor (GTO), and Insulated Gate Bipolar Transistor (IGBT) in an AC-AC phase converter to connect to the grid is examined in this range. Non-linear and linear loads are used to represent the load on the AC Cycloconverter range. Based on the results of the modeling and analysis of the PV 1 kWp system, the AC Cycloconverter in the first stage may provide a frequency of 50 Hz with a voltage drop of 235.4 V for the line and 231.9 V for the non-linear, which meets the AC Cycloconverter criterion.